Analisis Program Kerja Sama Regional Sosek Malindo dengan Human Trafficking Melalui Badan Pengelola Perbatasan Daerah - Adhe Fadli Farhan; Eki Darmawan; Kustiawan Kustiawan; Yudhanto Satyagraha Adiputra; Erta Kurnia Sapitri; Evi Natalia Togatorop; Nazira Junita Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study evaluates the effectiveness of the SOSEK MALINDO (Malaysian-Indonesian Socio-Economic) regional collaboration program in addressing human trafficking, coordinated by the Regional Border Management Agency (BPPD) of the Riau Islands Province (Kepri). The Riau Islands Province, which borders Malaysia and Singapore, is a strategic entry point vulnerable to transnational crimes, including human trafficking. The main factors driving the people of Kepri to choose illegal routes to become Indonesian Migrant Workers (TKI) to Malaysia are economic pressure, limited job opportunities, attractive promises from brokers (tekong), complex and expensive official bureaucracy, and a lack of accurate information about official procedures. This situation is exploited by human trafficking networks through hidden routes, illegal ports, and methods of illegal labor and sexual exploitation. Although SOSEK MALINDO aims to improve the socio-economic welfare of communities in border areas and indirectly functions to reduce vulnerability to human trafficking, this program does not specifically make human trafficking its main focus. The BPPD plays a very important role as a liaison in cooperation with the Indonesian National Police, Immigration, and BP3MI for prevention and supervision. However, the BPPD faces challenges such as limited funding, overlapping authority between institutions, and a lack of accurate data on human trafficking. Strategic recommendations include making human trafficking a primary focus of the SOSEK MALINDO forum agenda, establishing a dedicated cross-border human trafficking task force, strengthening the BPPD's role in coordination and information gathering, and involving local communities, NGOs, and international organizations in mitigation efforts.